2013
DOI: 10.1007/s00787-013-0379-9
|View full text |Cite
|
Sign up to set email alerts
|

The child behavior checklist dysregulation profile predicts adolescent DSM-5 pathological personality traits 4 years later

Abstract: Emotional dysregulation in childhood has been associated with various forms of later psychopathology, although no studies have investigated the personality related adolescent outcomes associated with early emotional dysregulation. The present study uses a typological approach to examine how the child behavior checklist-dysregulation profile (CBCL-DP) predicts DSM-5 pathological personality traits (as measured with the personality inventory for the diagnostic and statistical manual of mental disorders 5 or PID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 42 publications
7
62
0
Order By: Relevance
“…Longitudinal studies also suggest that the majority of children who meet CBCL-DP criteria develop various forms of psychopathology later on and become severely impaired in adulthood [5,17,45,48,49]. For example, Althoff et al [45] found that the CBCL-DP condition in children is associated with a 1-5% risk of anxiety, mood, disruptive behavior and drug abuse disorders later in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies also suggest that the majority of children who meet CBCL-DP criteria develop various forms of psychopathology later on and become severely impaired in adulthood [5,17,45,48,49]. For example, Althoff et al [45] found that the CBCL-DP condition in children is associated with a 1-5% risk of anxiety, mood, disruptive behavior and drug abuse disorders later in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Althoff et al [45] found that the CBCL-DP condition in children is associated with a 1-5% risk of anxiety, mood, disruptive behavior and drug abuse disorders later in adulthood. Recently, De Caluwé et al [48] have suggested that children assigned to the CBCL-DP group are at risk for elevated scores on a wide range of DSM-5 personality pathology features, including higher scores on hostility, risk taking, deceitfulness, callousness, grandiosity, irresponsibility, impulsivity and manipulativeness. Although the present study does not contrast these findings, SDQ-DP longitudinal studies are needed to help delineate vulnerability conveyed by this dysregulation phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study that used a typological approach to examine how the CBCL-DP in children predicted pathological personality traits across a time span of 4 years, showed that children with the CBCL-DP were at-risk for elevated scores on a wide range of personality pathological features, including higher scores on hostility, risk taking, deceitfulness, callousness, grandiosity, irresponsibility, impulsivity and manipulativeness (De Caluwè et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DSM-5 traits as assessed with the PID-5 explain a substantial amount of variance in DSM-IV personality disorders, underscoring the PID-5 traits' validity for predicting DSM-IV personality disorders . A recent study (De Caluwé, Decuyper, & De Clercq, 2013) showed that the PID-5 can be reliably and validly administered in adolescence using maternal ratings. In the present study, maladaptive personality traits in adolescence were assessed using both self-and maternal-rated PID-5 scales.…”
Section: Inventory Of Callous-unemotional Traitsmentioning
confidence: 99%